MARKETING PRODUCTS DURING THE COVID-19 PANDEMIC UTILIZING THE USE OF E-COMMERCE - Nst, Asrindah; Rizal, Muhammad (Universitas Dharmawangsa Medan, 2022)
ABSTRACTÂ The Covid-19 outbreak causes a global crisis, causing small and medium-sized businesses to face serious challenges. As a result, small businesses must respond to crises in an efficient manner. Small and medium-sized businesses will benefit from various digital technologies that are currently in development. Using online media to transform a business will provide benefits such as increasing the value of a product from a small to medium-sized business. The digital media that is used includes social media, marketplaces, Google Business, and others. The use of online media should make product marketing more efficient and increase the sale of any given product. The method of analysis that is used is a qualitative method with a descriptive method of study using a questionnaire and some actual and factual data.Â keywords: product marketing, digital media, the covid-19 pandemic